PHARMACOGNOSTICAL STANDARDIZATION AND HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FINGERPRINT OF ROOTS OF ANTHOCEPHALUS CADAMBA - KAVERIPAKAM SAISRUTHI; ADIKAY SREEDEVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Anthocephalus cadamba is a traditional medicinal plant which is valued for its benefits in the management of various ailments. The current study was aimed to provide requisite pharmacognostic details and high-performance thin-layer chromatography (HPTLC) fingerprint profile for the roots of A. cadamba. Methods: Pharmacognostic evaluation included examination of morphological and microscopic characters, physicochemical analysis, fluorescence study, preliminary phytochemical analysis, and HPTLC fingerprint. Results: The microscopic studies showed the presence of thick periderm, cortical zone, secondary phloem, and secondary xylem. Microscopic examination of root powder showed abundant fibers and vessel elements. The physicochemical analysis of root powder helped in the assessment of quality control parameters. Fluorescence analysis of root powder imparted characteristic colors on the treatment of the powder with different reagents. Preliminary phytochemical studies reported the presence of alkaloids, saponins, flavonoids, steroids, terpenoids, glycosides, tannins, and other phenolic compounds. The developed qualitative densitometric HPTLC fingerprint can be used as an identifying biochemical marker for ethanol extract of the roots of A. cadamba. Conclusion: The present study provides the information with respect to identification and authentication of crude drug and serves as a reference point for the proper identification of roots of this medicinal plant, thereby contributing to the scientific world of research.